Willingness to Communicate in English of Non-English Major University Students in Indonesia - Subekti, Adaninggar Septi (Lingua Cultura, 2019)
This research was conducted to investigate the willingness to communicate (WTC) of Indonesian learners of English as a second language (L2) at the university level. It was conducted based on several rationales. WTC in L2 was often regarded as the primary goal of language instructions, and there might be various factors influencing WTC in L2 and the two so-called strongest factors, namely learners’ perceived communication competence and communication apprehension, need to be investigated further to find out the degree to which they affected learners’ WTC. Besides, Indonesian learners’ low frequency of English use outside classroom contexts might lead them to be unwilling to make actual communication in English. Through probability random sampling, a total of 276 non-English major university students participated in the study, the data of which were analyzed using descriptive statistics and inferential statistics, correlation and regression, in SPSS 21. This research finds that learners have reported a high level of WTC, their perceived communication competence is found to be a strong predictor of learners’ WTC, communication apprehension is found to be correlated with WTC in just a moderate level, and despite experts’ supports on the importance of WTC in L2 learning, it surprisingly cannot predict learners’ L2 achievement.